2003
DOI: 10.1016/j.yhbeh.2003.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of nitric oxide and serotonin in aggressive behavior

Abstract: Nitric oxide (NO) modulates many behavioral and neuroendocrine responses. Genetic or pharmacological inhibition of the synthetic enzyme that produces NO in neurons evokes elevated and sustained aggression in male mice. Recently, the excessive aggressive and impulsive traits of neuronal NO synthase knockout (nNOS Ϫ/Ϫ ) mice were shown to be caused by reductions in serotonin (5-HT) turnover and deficient 5-HT 1A and 5-HT 1B receptor function in brain regions regulating emotion. The consistently high levels of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 108 publications
0
47
0
1
Order By: Relevance
“…First, we found significant associations between rs3782206 and working memory and attentional control, both of which have been associated with some symptoms of schizophrenia, such as distractibility, loosening of associations, disorganization, anger, aggression, and other socially inappropriate behaviors (Braver et al, 1999). In the previous animal studies, NOS1 gene knockout mice have showed very high levels of impulsive and aggressive behaviors (Chiavegatto et al, 2001;Chiavegatto and Nelson, 2003;Nelson et al, 2006). In the previous human studies, Reif et al (2009) found an association between a VNTR in the promoter region and many disorders characterized by impulsivity, such as attention deficit hyperactivity disorder, SCZ, and suicide attempt.…”
Section: Discussionmentioning
confidence: 67%
“…First, we found significant associations between rs3782206 and working memory and attentional control, both of which have been associated with some symptoms of schizophrenia, such as distractibility, loosening of associations, disorganization, anger, aggression, and other socially inappropriate behaviors (Braver et al, 1999). In the previous animal studies, NOS1 gene knockout mice have showed very high levels of impulsive and aggressive behaviors (Chiavegatto et al, 2001;Chiavegatto and Nelson, 2003;Nelson et al, 2006). In the previous human studies, Reif et al (2009) found an association between a VNTR in the promoter region and many disorders characterized by impulsivity, such as attention deficit hyperactivity disorder, SCZ, and suicide attempt.…”
Section: Discussionmentioning
confidence: 67%
“…Some animal studies reported that aggressive behavior was diminished in endothelial NO synthase-defi cient mice [23] , whereas it was increased in neuronal NO synthase-defi cient mice [23,24] . 5-HT, a key neurotransmitter system in aggression and impulsivity, has accounted for the relationship between aggressive behavior and NO synthase isoforms [25] . Moreover, mice lacking endothelial NO synthase showed enhanced 5-HT turnover in the frontal cortex and ventral striatum and increased 5-HT metabolite in the cerebellum [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated evidence has suggested an inverse relationship between serotonin level in cerebrospinal fluid (CSF) and brain with impulsivity, or escalated aggression, and suicide (Lee and Coccaro, 2001;van Praag, 1998). In rodents, some studies have shown a similar relationship with decreased serotonin and 5-HIAA levels associated with increased offensive aggression (Chiavegatto et al, 2001;Chiavegatto and Nelson, 2003;Ferrari et al, 2005;van der Vegt et al, 2003).…”
Section: Neurochemical Differencesmentioning
confidence: 99%
“…This type of offensive aggression can also be modulated by serotonin activity and drugs (Chiavegatto et al, 2001;Fish et al, 1999;Lyons et al, 1999;Miczek et al, 1998). Genetic manipulations that target serotonin-related genes, and on genes that affect serotonin receptor numbers also can change this form of aggression in rodents (Chiavegatto et al, 2001;Chiavegatto and Nelson, 2003;Dulawa et al, 2000;Fischer et al, 2000;Liu et al, 2007;Nelson et al, 2006;Saudou et al, 1994;Schiller et al, 2006;Stork et al, 2000;Wersinger et al, 2007). We also assessed defensive aggression by using the target-biting paradigm.…”
Section: Introductionmentioning
confidence: 99%